Modernization Of Madrasa Policy In Egypt And Indonesia - Hadi, Muhammad Fazlurrahman (Proceedings of Annual Conference for Muslim Scholars, 2019)
The Global competition has a long history that is marked by the enlightenment of the 18th century, especially Islamic education. There are currents called modernization of Islamic education, including Indonesia. However, it becomes important and interesting to study it not only from now on but how the modernization of Islamic education from its historical aspects. The existence of this research is expected to be able to describe the modernization of Islamic education in Indonesia and Egypt. This research was conducted using a literature research model (literature review), using a qualitative type. The discovery of figures who at that time were not well known, such as Rifa'ah al-Tahtawi, appeared to have not been much studied. The renewal of Islamic education in Indonesia that occurred at the beginning of the 20th century was also influenced by the thinking of figures in Egypt, such as the founder of the Adabiyah madrasa in Padang Panjang. The intermittent political upheaval in Egypt and Indonesia greatly influenced educational policies. The highest authority has not yet fully paid attention, although recently there have been some improvements made since Mubarak's leadership collapsed, not yet encouraging the advancement of educational institutions there. Almost the same thing also happened in Indonesia, since the reform era there have been many changes in the world of Islamic education, taking into account the salaries of civil servants and private teachers, but always leaving new problems or problems for education